Algorithms, Religious Authority, and Digital Da’wah: A Qualitative Study of Social Media in Indonesia - Isnain La Harisi; Marwan Mas’ud; Ali Imran; Muhammad Yusriel Amien (MASI Mandiri Edukasi, 2026)
The rapid expansion of social media has reshaped the landscape of Islamic da’wah in Indonesia, with algorithms playing an increasingly important role in the circulation of religious content. This exploratory qualitative study examines how platform algorithms influence the distribution of digital da’wah, how religious authority is renegotiated in online environments, and how Muslim users respond to algorithm-mediated religious messages. The study combines digital ethnography, social media content analysis, and an exploratory questionnaire involving seven active young social media users. The findings show that algorithms significantly shape the visibility of da’wah content and influence everyday encounters with religious messages. The study also identifies an authority paradox: although users continue to value preachers with strong religious education, the content they encounter most frequently is often determined by algorithmic visibility rather than scholarly depth. This situation produces a hybrid form of religious authority in which scholarship, communicative style, and platform performance increasingly intersect. Theoretically, this article contributes to digital religion studies by linking algorithmic mediation with the transformation of religious authority and audience reception. In practice, it highlights the need for credible digital da’wah that integrates scholarly rigor, Islamic communication ethics, and digital literacy in algorithm-driven environments.